Combinatorial treatment for unresectable unicentric Castleman disease. (18th July 2021) - Mohan, Meera; Meek, James C.; Meek, Mary Elizabeth; Broadwater, Ralph; Alapat, Daisy; van Rhee, Frits
Abstract: Unresectable, symptomatic unicentric Castleman disease (UCD) can represent a formidable therapeutic challenge. UCD masses are often highly vascularized offering the opportunity for therapeutic embolization. Herein, we report on 6 patients in which therapeutic embolization was combined with other medical interventions including surgery (n = 3), rituximab (n = 6), cryoablation (n = 2), and chemotherapy (n = 3). Five patients had significant tumor volume reductions (median: 83.2%; range: 76.7‐100). All five responding patients had resolution of symptomatology. There were no serious complications in the patients who received embolization and proceeded to surgery. In conclusion, effective disease and symptom control can be obtained in patients with symptomatic, unresectable UCD by combining different therapeutic interventions.